Хронологія та періодизація волгодонської бабинської культури - Мимоход, Р.О. (Археологія і давня історія України, 2021)
Стаття присвячена хронології та періодизації
волго-донської бабинської культури. Встановлено,
що культура має два етапи розвитку і датується
XXII—XX cal. BC. The article is devoted to establishing the chronology
and periodization of the Volga-Don Babyne culture,
which is the eastern part of the Babyne cultural circle.
VDBC has changed from a «Krivaya Luka cultural
group» to a full-fledged culture. An important contribution
to this process was made by V. V. Otroshchenko.
The basis for establishing the chronology and development
of the periodization of VDBC are stratigraphic
data, the presence of narrowly dated categories of
inventory and a series of radiocarbon dating. Stratigraphic
data show that the burials of the VDBC in the
mounds follow the catacomb and Poltavka mounds and
are covered by the tombs of the beginning of the Late
Bronze Age. This fact allows us to date it to the end of
the Middle Bronze Age. The sequence of cultures in the
Lower Volga region is catacomb / Poltavka — VDBC —
chariot cultures. There is a series of stratigraphic connections
between the burials of post-catacomb cultural
formations, where Babyne burials overlap the Lola
ones and vice versa. This also confirms the dating of
the VDBC within the post-catacomb horizon. Due to
the presence of narrowly dated categories of inventory
in the VDBC inventory complex (buckles, a bar with
two constrictions, crates, set-arrow-makers, petal and
horn beads, a bronze cap of Caucasian origin, etc.) it
is possible to develop a two-stage periodization of the
culture. Most of the diagnostic inventory belongs to the
early stage. Two periods of VDBC correspond to two
phases (early and advanced) of the post-catacomb block
development. VDBC can be synchronized with the first
and second stages of the Lola culture and DDBC, as
well as with the first stage of the DPBC. The VDBC
radiocarbon database contains 18 dates, of which 7 are
AMS dates. All of them show a good degree of convergence,
which makes it possible to date the culture of
the XXII—XX centuries BC. Comparison of this series
with 14C data from the other Babyne cultures and the
Lola cultural circle confirms the established synchronization
lines.